Long-term adherence to growth hormone therapy in a large health maintenance organization cohort. (February 2019) - Farfel, Alon; Shalitin, Shlomit; Morag, Nira; Meyerovitch, Joseph
Abstract: Objective: Adherence to treatment regimen is a key factor in the success of Growth Hormone (GH) therapy. Our objective was to assess the long time adherence to treatment in a large cohort of patients. Design: It is a retrospective study. The data was collected from a single central computerized data center well maintained and checked for quality. All patient aged 1–16 years, treated with GH during 2006–2015 for >2 years, who were insured by "Clalit" Health Maintenance Organization. Adherence was measured by the number of months of pharmacy purchased GH annually: good (11−12), moderate (7–10), and poor (<7) months per year. Results: 2263 patients (59% males) were treated for >2 years. Mean age at treatment initiation was 8.3 ± 3.6 years, 74% were secular Jews, 6.8% ultra-religious Jews and 18.9% of Arab origin. Only 30% of patients had good adherence to GH therapy. Patients who started treatment before age 8 years had poorest adherence rate. No association was found between adherence to GH therapy and gender or socioeconomic status. In a multivariate analysis (gender, age groups, ethnicity and clinic SES) we found the ultra-religious population had higher risk for non adherence (OR 2.16, CI 95% 1.46–3.19). The poorest adherence by age was in the youngest patients. In patients treated for >5 years (n = 668), adherence rate declined slightly over the years. Conclusions: Long term adherence to GH therapy is suboptimal. Measures for improving adherence especially among younger and ultra- religious patients are needed. Highlights: Only 30% of patients treated with Growth Hormone, had good long term adherence. Long term adherence to GH therapy is lower among younger patients. Adherence declined slightly over the years in patients treated for >5 years.